2016
DOI: 10.15567/mljekarstvo.2016.0304
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of κ-casein and β-lactoglobulin genes in Busha and Holstein Friesian dairy cows in Serbia

Abstract: The aim of this study was to determine the distribution of κ-casein (κ-CN) and β-lactoglobulin (β-Lg) genotypes in the autochtonous (Busha) and dairy (Holstein-Friesian, HF) cattle breeds with PCR-RFLP (polymerase chain reaction -restriction fragment length polymorphism). For the amplification of κ-CN and β-Lg gene fragments specific primers were used. After digestion with specific endonucleases genotypes were determined for both genes in 18 Busha and 19 HF cows. The results showed that κ-CN gene was represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Many other authors (Taha and Punan, 1993, Dogru and Ozdemir, 2009, Dokso et al, 2014, Djedović et al, 2015 found that the frequency of the AB genotype in the Brown Swiss breed was higher compared to other genotypes, while Potočnik (2015) determined a higher share of BB genotypes compared to AA and AB in this breed. The higher frequency of BB genotype in Jersey cattle (0.772) with absent of opposite AA genotype is reported by Ren et al, 2011 Ho: observed heterozygotes, He: expected heterozygotes on the basis of Hardy-Weinberg, χ2 =chi-square value Similar to our research, Djedović et al (2015), Maletić et al (2016), Brka et al (2010) also obtained that heterozygote genotype of κ-casein (AB) was dominant in Busha breed. Only in the research of Ivanković et al (2011) determined dominance of BB homozygote.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Many other authors (Taha and Punan, 1993, Dogru and Ozdemir, 2009, Dokso et al, 2014, Djedović et al, 2015 found that the frequency of the AB genotype in the Brown Swiss breed was higher compared to other genotypes, while Potočnik (2015) determined a higher share of BB genotypes compared to AA and AB in this breed. The higher frequency of BB genotype in Jersey cattle (0.772) with absent of opposite AA genotype is reported by Ren et al, 2011 Ho: observed heterozygotes, He: expected heterozygotes on the basis of Hardy-Weinberg, χ2 =chi-square value Similar to our research, Djedović et al (2015), Maletić et al (2016), Brka et al (2010) also obtained that heterozygote genotype of κ-casein (AB) was dominant in Busha breed. Only in the research of Ivanković et al (2011) determined dominance of BB homozygote.…”
Section: Resultssupporting
confidence: 87%
“…For high productive Holstein Friesian breed some authors (Volkandari et al, 2017, Tanaskovska et al, 2016, Khaizaran and Razem, 2014, Dokso et al, 2014, Ren et al, 2011 determined higher frequency of AA genotype than AB and BB genotypes, what is similar to result obtained for Brown Swiss breed. Other authors, as Doosti et al (2011), Gouda et al (2013), Maletić et al (2016) reported for Holstein breed the highest frequency of AB genotype κ-casein.…”
Section: Resultsmentioning
confidence: 78%
“…These sires are the ancestors of the nowadays bulls used in artifi cial insemination programs of cows from which we collected the samples for our investigation. The relationship between various milk proteins, milk yield and milk composition (protein and fat concentrations) was assessed by different authors (beta-casein: [28,29,31,36,44,45]; kappa casein: [46,47]). In order to assess the relationship in Serbian HF cows we collected the relevant data for 106 animals.…”
Section: Discussionmentioning
confidence: 99%
“…The protein part of cow raw milk consists of casein (about 80 %) and serum (about 20 %) fractions, which are encoded by six main protein genes: αS1-casein (CSN1S1), β-casein (CSN2), αS2-casein (CSN1S2), κ-casein (CSN3), α-lactoalbumin (LALBA), β-lactoglobulin (LGB) (Gurses et al, 2016;Mahmoudi et al, 2020;Maletić et al, 2016). In recent decades the influence of CSN3 gene on cattle milk yield, milk composition and technological properties have been widely studied.…”
Section: Introductionmentioning
confidence: 99%